Survey of attitudes toward performing and reflecting on required team service-learning (SASL): psychometric data and reliability/validity for healthcare professions students in preclinical courses - Van Winkle, Lon J.; Rogers, Shane L.; Thornock, Bradley O.; Schwartz, Brian D.; Horst, Alexis; Fisher, Jensen A.; Michels, Nicole (Frontiers in Medicine, 2023)
Purpose Previously we assessed healthcare professional students’ feelings about team-based learning, implicit bias, and service to the community using an in-house paper survey. In this study, we determined whether this survey is a reliable and valid measure of prospective medical students’ attitudes toward required service-learning in an Immunology course. To our knowledge, no published questionnaire has been shown to be dependable and useful for measuring such attitudes using only eight survey items. Methods Fifty-eight prospective medical students in Colorado (CO) and 15 in Utah (UT) completed the same Immunology course using remote technology. In addition to the usual course content, students were required to write critical reflections on required team service-learning. On the last day of class, they completed the survey of attitudes toward service-learning (SASL). Results Data analyses found Cronbach’s alpha values of 0.84 and 0.85 for the surveys of UT and CO students, respectively. Factor analysis of CO student data revealed only one Eigenvalue greater than one (3.95) justifying retention of a single factor termed “attitudes toward required service-learning.” In addition, CO students’ attitudes toward community service were highly positive, while UT students’ attitudes were nearer neutral (p < 0.0001). Conclusion Our factor analysis and good Cronbach’s alpha values support the conclusion that the SASL was a reliable measure of prospective medical students’ attitudes toward required team service-learning for an Immunology course. Moreover, we used the SASL to distinguish these attitudes in CO versus UT students, and, thus, the SASL appears to be a valid measure of this difference. Calculation of similarly good Cronbach’s alpha values – for a predecessor of the SASL among pharmacy, masters, and medical students at another institution – indicates that the SASL may be useful more widely. However, the reliability and validity of the SASL needs to be demonstrated more rigorously for other healthcare students at different universities.